2019
DOI: 10.21203/rs.2.16315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of initial periodontal therapy on the prevalence of Epstein-Barr virus DNA and Porphyromonas gingivalis in Japanese chronic periodontitis patients

Abstract: Background Initial periodontal therapy (IPT) is cornerstone of periodontal therapy and the first step to control of periodontal risk factors. Scaling and root planing are used to treat root surface irregularities and remove virulent factors caused by periodontal pathogens. This procedure also incorporated into periodontal surgery. To elucidate the effects of IPT on prevalence of Epstein-Barr virus (EBV) DNA and Porphyromonas gingivalis , we used subgingival plaque samples from chronic periodontitis (CP) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These authors identified large amounts of infiltrated EBV-infected cells mostly overlapping with CD138+ plasma cells [ 60 ]. In contrast, Kato et al [ 61 ] found that initial periodontal therapy was effective in reducing the coexistence of EBV and P . gingivalis in the subgingival plaque of periodontitis patients, though it could not completely eradicate it.…”
Section: Discussionmentioning
confidence: 96%
“…These authors identified large amounts of infiltrated EBV-infected cells mostly overlapping with CD138+ plasma cells [ 60 ]. In contrast, Kato et al [ 61 ] found that initial periodontal therapy was effective in reducing the coexistence of EBV and P . gingivalis in the subgingival plaque of periodontitis patients, though it could not completely eradicate it.…”
Section: Discussionmentioning
confidence: 96%